Odin og Hvide Krist: Om Sune Aukens bog Sagas spejl. Mytologi, historie og kristendom hos N. F. S. Grundtvig, København, 2005 - Lyby, Thorkild C. (Grundtvig-Studier, 2005)
Odin og Hvide Krist: Om Sune Aukens bog Sagas spejl. Mytologi, historie og kristendom hos N. F. S. Grundtvig, København, 2005 [Odin and the White Christ: On Sune Auken ’s book Sagas spejl. Mytologi, historie og kristendom hos N. F. S. Grundtvig, Copenhagen, 2005] By Thorkild C. Lyby The article gives a short account of Sune Auken’s published doctoral thesis, Sagas spejl. Mytologi, historie og kristendom hos N. F. S. Grundtvig [Saga’s mirror. Mythology, history and Christianity in N. F. S. Grundtvig] in which he investigates Gr’s preoccupation with Norse mythology and its relationship to history and Christianity. In Auken’s view Norse mythology during the years 1806-10 became something like an actual religion for Gr, a basis for an entire concept of life. As he could not give up traditional Christianity, he was forced to try to harmonise it with Christianity. In this attempt he failed, which was the main reason of his mental breakdown in 1810. After 1815 he did not work theoretically with the myths, but in his poetry they still played an important role. Not until 1832 was a sort of harmony established between his theoretical and his poetic relationship to the myths. Furthermore, the article gives a short account of the public examination on 3 June 2005, when Auken defended his thesis. The contributions of the different opponents at this occasion are mentioned. Finally, the author elaborates his own contribution as the third opponent. Two points are discussed: (a) What did Gr mean by the expression “the image of God”? (b) Is Auken’s view of Norse mythology as an alternative religion justified? Would it not be better to characterize it as “quasi-religious” than to label it “a religion”?